Answer:
208.00015
Step-by-step explanation:
Use a calculator. I'm sorry, there's no other way
you first plug (substitute) in y
-3x - 3(-5x-17)=3
then distribute
-3x+15x+51=3
now combine like terms
12x+51=3
subtract to get 12x by itself
12x=3-51 or 12x=-48
lastly divide by 12 to find x
12x/12=-48/12
x=-4
now find y by plugging x into the other equation
y=-5(-4)-17
y=3
(-4,3)
Answer:
your answer is correct.
Step-by-step explanation:
For the purpose here, we'll call the missing point on the arc through Z point X.
Essentially, you want to make ΔXYZ ≅ ΔLMN by SSS. The construction so far ensures LM ≅ MN ≅ XY ≅ YZ. By copying the length LN to XZ, you ensure the congruence of the remaining sides of the triangles.
Then ∠XYZ ≅ ∠LMN because corresponding parts of congruent triangles are congruent.
In short, XZ needs to be the same distance as LN.
I hate math its so hard for no reason